Building reputational capital - Jackson, Kevin T. (Oxford University Press, 2004)
In the aftermath of scandals such as those at Enron and WorldCom, there is a growing suspicion of the corporate world. For this reason it is more important than ever for firms to maintain a good reputation. In Building Reputational Capital, Kevin T. Jackson offers a practical guide to taking the high road--the only path that leads to lasting success